COST-BENEFIT ANALYSIS OF FROST PROTECTION METHODS - Fike, Matej; Fekonja, Mateja; Smrekar, Miha (Journal of Energy Technology, 2024)
Agricultural losses due to frost are high in various parts of the world, and in Slovenia, frost damage has frequently occurred in recent decades. Multiple methods for preventing frost damage exist and have been researched more or less extensively. Despite this, frost prevention measures are relatively sparsely used in Slovenia. This article aimed to review and compare active frost prevention techno- logy for a case study of a typical fruit farm in Slovenia, based on a cost-benefit analysis. Most of the active methods require either large capital investment or have a high annual cost. According to our analysis, burning wood, used in Slovenia to battle frost damage in orchards and vineyards, proved to be the most cost-effective method, which is probably why it remains in wide use.